EFFECT OF FAMILY FACTOR AND CHILDREN’S SCHOOL READINESS IN INTEGRATED WASTE TREATMENT PLACES: PATH ANALYSIS - Nur Rochimah; Myrnawati Crie Handini; Hapidin Hapidin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
Many factors can affect children's school readiness, one of which is the family as their closest environment. This research aimed to analyze the effect of family socioeconomic status, family stress, and parental involvement on children's school readiness. This research involves 113 parents and students of group B Kindergarten in the Integrated Waste Processing Site (TPST) in Bantargebang District, Bekasi City, West Java Province. This sample was obtained using the multistage random sampling technique. This study uses path analysis techniques. This study indicates that socioeconomic status, family stress, and parental involvement do not directly affect Children’s school readiness. However, family socioeconomic status has a negative direct effect on family stress, and family stress can also have a negative direct effect on parental involvement in children's education. These findings imply that it is important to create a warm and supportive family environment to optimally carry out their roles and functions in children's education.